Islamic Boarding School Curriculum in Indonesia: A Case Study in Islamic Boarding School in South Kalimantan - Yakin, Husnul (Al-Hikmah, 2012)
Islamic boarding school as traditional Islamic education institution is an invaluable part of Indonesian national education system. This education institute has been able to show itself freely according to society needs and epoch demand without loosing its essential identity as tafaqquh fiddin institution. The important factor that sustains this condition can be seen from the curriculum aspect. Therefore, this article is intended to investigate Islamic boarding school curriculum in Indonesia, especially at Islamic boarding school case in South Kalimantan. This Islamic boarding school curriculum is focused on written curriculum both scientific study and the specific books. This study also shows how Islamic boarding school curriculum model as responding to national education curriculum development in Indonesia.